Seni Tari di Era Virtual dan Augmented Reality - Citrawati, A.A.I.A; Oktavianus; Nurmalena; Irdawati; Herwanfakhrizal (The Indonesian Journal of Computer Science, 2024)
The art of dance has been revolutionized in the era of virtual and augmented reality (VR and AR), bringing about significant transformations in presentation, interaction and audience participation. This article explores the impact of these technologies on the art of dance, investigating how VR and AR are changing artists' creativity, enriching the audience experience, and enabling the development of new dance styles. In this context, dance is not only a witness to change, but also the main actor in combining traditional beauty with modern innovation. The method applied is "Library Research" which is sourced from national and international journals through platforms such as scholar.google.com, www.elsevier.com, and www.crossref.org. As a result, the art of dance in the era of virtual and augmented reality does not maintain its traditional richness, but also becomes an agent of innovation that combines the beauty of art with technological progress.